2002
DOI: 10.1089/08942680252908566
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Accumulation during Small Animal, Whole Body Plethysmography: Effects on Ventilation, Indices of Airway Function, and Aerosol Deposition

Abstract: Barometric (whole body) plethysmography is used to examine changes in ventilation and breathing pattern in unrestrained animals during exposure to therapeutic or toxic aerosols. Whole body plethysmographs (WBP) may be operated with a bias flow in order to maintain an adequate supply of oxygen and remove expired CO(2). However, some aerosol generation and delivery methods may require operation of the WBP without bias flow, which would artificially deplete aerosol concentration. Under these conditions, expired C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…This observation is in apparent agreement with the findings of Mautz et al (1985a) who demonstrated increased histopathology in the bronchoalveolar duct region of O 3 exposed rats that were exercised. Increased aerosol deposition has also been reported in animals rebreathing CO 2 (Kimmel et al, 2002). In contrast, however, studies in exercised hamsters exposed to a sulfur-colloid aerosol showed no difference in the particle deposition pattern compared to hamsters that were not active during exposure (Harbison and Brain, 1983).…”
Section: Methods For Enhancing the Sensitivity Of Ventilatory Testsmentioning
confidence: 95%
“…This observation is in apparent agreement with the findings of Mautz et al (1985a) who demonstrated increased histopathology in the bronchoalveolar duct region of O 3 exposed rats that were exercised. Increased aerosol deposition has also been reported in animals rebreathing CO 2 (Kimmel et al, 2002). In contrast, however, studies in exercised hamsters exposed to a sulfur-colloid aerosol showed no difference in the particle deposition pattern compared to hamsters that were not active during exposure (Harbison and Brain, 1983).…”
Section: Methods For Enhancing the Sensitivity Of Ventilatory Testsmentioning
confidence: 95%
“…The changes in pressure are due to gas compression from breathing mechanics of the animal and gas conditioning from heating and humidification of inspired air, with the gas conditioning being the predominate source for the pressure change (Lundblad et al, 2002;Mitzner & Tankersley, 1998). This method has been used by previous researchers (Kimmel et al, 2002;Mortola & Seifert, 2002;Seifert & Mortola, 2002a, 2002b, 2002cStrohl et al, 1997;Tankersley et al, 1997;Weideman et al, 1996) to measure respiratory parameters in small animals. The technique is advantageous because it is noninvasive and nonstressful, thus allowing repetitive monitoring of the same rats over the entire period of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…2% in 10 min from expiration (guinea pig) but does not alter significantly the baseline respiratory parameters. 10 With the contribution of CO 2 from the smoke (up to 0.56%), CO 2 levels high enough to alter ventilation may be achieved, particularly near the end of a 10-minute interval between smoke replenishment. However, temporal variations in the observed breathing pattern changes did not appear to coincide with purging the plethysmograph.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments showed that in 10 min the accumulation of CO 2 in the plethysmographs did not significantly change baseline respiratory parameters in guinea pigs. 10 After 30 min of exposure, each plethysmograph was flushed at a rate of 9 l min −1 for 3 min with fresh air to clear the smoke. Breathing parameters were recorded for an additional 30 min.…”
Section: Exposure System and Smoke Characterizationmentioning
confidence: 99%
See 1 more Smart Citation